2000
DOI: 10.1097/00007890-200012270-00001
|View full text |Cite
|
Sign up to set email alerts
|

The Safety and Efficacy of Laparoscopic Live Donor Nephrectomy: A Systematic Review1

Abstract: The ASERNIP-S Review Group concluded that the evidence-base for laparoscopic live donor nephrectomy was inadequate to make a safety and efficacy recommendation. Clinical and research recommendations were developed regarding the introduction and current practice of this procedure in Australia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
71
1
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(75 citation statements)
references
References 38 publications
2
71
1
1
Order By: Relevance
“…But to date, no study has shown a significant difference in rejection rate and long-term survival when comparing laparoscopic to open kidney grafts (2,7,(10)(11)(12)(13)(14)(19)(20)(21)(22). In our analysis, the procurement mode did not affect acute rejection incidence and long-term graft survival either.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…But to date, no study has shown a significant difference in rejection rate and long-term survival when comparing laparoscopic to open kidney grafts (2,7,(10)(11)(12)(13)(14)(19)(20)(21)(22). In our analysis, the procurement mode did not affect acute rejection incidence and long-term graft survival either.…”
Section: Discussioncontrasting
confidence: 57%
“…Multiple studies have shown that laparoscopic nephrectomy is considerably gentler for the donor, because it is associated with less postoperative pain, a shorter length of hospital stay, improved cosmesis, and faster return to work and activities of daily living (2). Some investigators have even suggested that the availability of the minimally invasive procurement mode has significantly contributed to the recent increase of live kidney donations in the United States (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…The recently observed increase in live kidney donations in the United States is thought to be, at least in part, the result of the introduction of laparoscopic donor nephrectomy, which was shown to result in a shorter length of hospital stay, less post-operative pain, improved cosmesis and more rapid return to work and to normal activities of daily life for the kidney donors (20)(21)(22)(23)(24). Hence, it is not surprising that the laparoscopic procurement mode has rapidly become the preferred approach to the live kidney donor for transplantation of adult recipients (2).…”
Section: Discussionmentioning
confidence: 99%
“…Various studies and reviews have demonstrated a complication rate ranging from 0% to 38% using the open procurement approach and 0% to 30% with the conventional laparoscopic approach [22,23]. More recent studies have reported complications of less than 10% in conventional laparoscopic donor nephrectomy [24,25].…”
Section: Morbiditymentioning
confidence: 99%